Insights Into Extracellular Vesicles as Biomarker of NAFLD Pathogenesis - Garcia-Martinez, Irma; Alen, Rosa; Rada, Patricia; Valverde, Angela M. (Frontiers in Medicine, 2020)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease around the world estimated to affect up to one-third of the adult population and is expected to continue rising in the coming years. NAFLD is considered as the hepatic manifestation of the metabolic syndrome since it is strongly associated with obesity, insulin resistance, type-2 diabetes mellitus (T2DM) and cardiovascular complications. Despite its high prevalence, factors leading to progression of NAFLD from simple steatosis to non-alcoholic steatohepatitis (NASH), cirrhosis and, ultimately hepatocellular carcinoma (HCC) remain poorly understood. To date, no treatment has proven efficacy and also no reliable method is currently available for diagnosis or staging of NAFLD beyond the highly invasive liver biopsy. Recently, extracellular vesicles (EVs) have emerged as potential candidate biomarkers for the diagnosis of NAFLD. EVs are circulating, cell-derived vesicles containing proteins and nucleic acids, among other components, that interact with and trigger a plethora of responses in neighbour or distant target cells. Several mechanisms implicated in NAFLD progression, such as inflammation, fibrosis and angiogenesis, all related to metabolic syndrome-associated lipotoxicity, trigger EVs production and release by liver cells. As hepatocytes represent around 80% of the liver volume, in this review we will focus on hepatocyte-derived EVs (Hep-EVs) as drivers of the interactome between different liver cell types in NAFLD pathogenesis, as well as in their role as non-invasive biomarkers for NAFLD diagnosis and progression. Based on that, we will highlight the research that is currently available on EVs in this topic, the current limitations and future directions for implementation in a clinical setting as biomarkers or targets of liver disease.